Contributions of bogie aerodynamic loads to the crosswind safety of a high-speed train. Issue 228 (September 2022) - Liu, Dongrun; Liang, Xifeng; Zhou, Wei; Zhang, Lei; Lu, Zhaijun; Zhong, Mu
Abstract: Vehicle lightweighting and anti-crosswind performance are incompatible. Therefore, understanding the contribution of the aerodynamic load of each vehicle component to train crosswind safety is critical to supporting lightweight vehicle design. In this study, this challenge is focused on and the contribution of the bogie system to the train crosswind safety and dynamic performance is systematically investigated using Computational Fluid Dynamics ( CFD ) simulations and Multi-body Dynamic simulations ( MBS ) in different wind scenarios. In addition, the influence of the wheelset rotation and the independence of the aerodynamic loads of the car-body and the bogie on the numerical prediction of train crosswind safety risk and dynamic behavior is further studied. The results reveal that the wheelset rotation and the independent loading have a significant impact on the numerical prediction of the train's crosswind safety risk and dynamic response. Current numerical predictions ignore the wheelset rotation, and independent loading may lead to misjudgment of the crosswind safety and stability of a train. As a result, it is suggested to adopt the partition loading strategy in the multi-body dynamics assessment of high-speed train crosswind safety. Highlights: The partition loading strategy in the multi-body dynamics assessment of high-speed train crosswind safety is proposed. The impact and contribution of the bogie system to the numerical prediction of train crosswind safety risk is systematically investigated. The independence of the aerodynamic loads of the car-body and the bogie on the numerical prediction of train dynamic behavior is studied.